Exploring the Acceptability of Traditional Medicine Clinic Implementation in Indonesian Public Health Centers - Sri Mumpuni Yuniarsih; Retna Siwi Padmawati; Ema Madyaningrum; Yodi Mahendradhata (Nurse Media: Journal of Nursing)
Background: The World Health Organization (WHO) encourages the integration of traditional medicine (TM) into healthcare services, recognizing its cultural importance in countries like Indonesia. However, this integration needs improvement to ensure quality and accessibility. Previous research has primarily focused on policy implementation or health outcomes with limited exploration of the acceptability of TM clinics in Primary Health Centers (PHCs) from the perspectives of stakeholders using the Theoretical Framework of Acceptability (TFA). Operational and ethical challenges of this integration remain underexplored.